Implikasi Etika dalam Profil dan Strategi Penipuan Online dalam Transaksi e-Commerce di Ranah Cybercrime - Dylan Kaisar Hasya; Destania Safitri; Dewangkoro Ramadhan Putra; Farhan Bilawa Gita Maulana; Nur Aini Rakhmawati (Jurnal Manajemen Riset Inovasi, 2024)
. In today's rapidly evolving digital era, e-commerce has emerged as a cornerstone of global trade. However, the proliferation of online fraud incidents has given rise to significant ethical concerns. This study delves into the ethical ramifications of online fraud profiles and tactics within the cybercrime domain, particularly their impact on the e-commerce ecosystem. Ethical considerations play a pivotal role in shaping behavior within e-commerce, safeguarding consumers, and guiding the formulation of effective policies by both e-commerce entities and governments. This research scrutinizes the phenomenon of online fraud in e-commerce transactions through a survey involving two respondent groups: Information Systems students at ITS and students from other departments. The survey results reveal that online fraud inflicts substantial emotional distress on victims, including feelings of panic, anger, and sadness. Financial losses and the potential exposure of sensitive data are prevalent repercussions of online fraud, eroding consumer trust and prompting questions about the ethical conduct of fraudsters. To address these issues, recommendations encompass heightened awareness of online fraud risks, increased transparency among e-commerce sellers, streamlining fraud reporting procedures, and a commitment to upholding higher standards of business ethics. The overarching objective is to foster a more ethical, secure, and sustainable e-commerce environment. In summary, this research offers comprehensive insights into how respondents perceive and experience online fraud in Indonesian e-commerce transactions, providing valuable guidance for more effective mitigation.